Digital divides? UK Film Council strategy and the digital screen network - Boyle, Raymond (International Journal of Media & Cultural Politics, 2015)
Abstract In retrospect it is easy to identify digital technology and the disruptive nature of the Internet as two key factors shaping the broader screen landscape over the last decade or so, but how did organizations deal with that process at the time? This article examines the role that digitization and its wider ramification across the UK film industry’s patterns of distribution and exhibition played in both the strategic thinking and the operational practice of the UK Film Council (UKFC) during its lifetime (2000–2011). It draws on interviews with key policy shapers and asks whether the UKFC was too slow to identify the transformative impact that digital would have on all areas of the film industry. By focusing on the origins and implementation of the Digital Screen Network, this article examines the impact of this programme on the UK film industry. It also offers insight into the organizational challenges of shaping digital film policy in an international industry.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9tYWNwLjExLjEuM18x